Development of technology for production of functional fruit drinks - Pavlenko, Svitlana; Verkhivker, Yakov; Myroshnichenko Оlena (Technology audit and production reserves, 2021)
The object of research is the technology of functional fruit and vegetable juice products enriched with collagen. The subject of research is various types of collagen, formulations and parameters of technological operations for the production of functional juice drinks. The research is aimed at the develop technology, recipes for a new assortment of fruit and vegetable drinks enriched with collagen. Also it is aimed at the preserve the functional properties of collagen in canned juice products after high-temperature processing and create food products for everyday consumption to solve age-related and other problems associated with human health. In the course of the study, standard methods were used to determine the organoleptic indicators of various types of collagen, juice products, as well as to determine the mass fraction of moisture, carbohydrates, fats, proteins in the developed fruit and vegetable drinks enriched with collagen. Also, to confirm the presence and preservation of collagen in finished products, the electrophoresis method was used to determine the atomic mass unit of the constituent substances after complete drying of the samples. The proposed methods make it possible to assess the quality of the developed collagen-enriched drinks, prove the presence and preservation of a biologically active additive in the finished product after using the sterilization mode parameters – temperature and time, when receiving canned products. The developed formulations and technology make it possible to consider functional fruit and vegetable juice-containing products enriched with a biologically active additive collagen as effective and useful. An easily digestible food product for everyday consumption is proposed for solving age-related and other problems related to human health, with regulation of the pH value for effective use of the beneficial properties of this additive. In contrast to existing functional juice products, the proposed formulations and technology make it possible to obtain juice-containing fruit and vegetable blended products with a biologically active additive collagen. The technology minimizes the impact of collagen on the organoleptic characteristics of the developed recipe compositions of finished products and preserves its beneficial biologically active properties in the finished canned product after heat sterilization.